PSYCHOLOGICAL FACTORS IN THE FORMATION OF CIVIC AWARENESS AMONG UNIVERSITY STUDENTS (Psychology Travelogs, 2025)
This article is devoted to analyzing the psychological mechanisms underpinning the development of civic awareness among higher education students. Civic awareness is conceptualized as an integrative personal characteristic, encompassing cognitive, motivational-value, and emotional-volitional components, which together ensure young people’s ability to interact consciously with society and to take responsible part in its advancement. It is substantiated that the interaction of motivational, value-semantic, and cognitive (critical) mechanisms plays a decisive role in shaping active civic engagement, determining the structural integrity of civic competence. Special attention is given to the significance of psychological disciplines, which, by influencing motivational domains, value orientations, and critical thinking, facilitate the enhancement of social responsibility, the development of empathy, reflexivity, and the comprehension of the individual’s role in societal transformations. Empirical data from a student survey confirmed that 55% of respondents consider psychological education an important factor in establishing their civic stance, while 70% participate in civic initiatives. Furthermore, it is determined that profound integration of psychological knowledge into the curriculum, the use of case-study methodology, media literacy trainings, and role-play simulations contribute to the development of critical thinking, empathy, tolerance, and skills for constructive civic participation. It is established that motivational-value processes and critical thinking are closely intertwined, and systemic utilization of psychological tools can provide a basis for the formation of mature civic consciousness among youth, oriented toward responsible decision-making regarding themselves and society.
Keywords: psychological education; value orientations; critical thinking; motivation; social responsibility; civic awareness; competence